Penyesuaian Kurikulum Hukum Pidana dan Tantangan dalam Mengintegrasikan Materi KUHP Nasional ke dalam Pendidikan Tinggi Hukum di Indonesia - Darwin Steven Siagian (Jurnal Ragam Pengabdian, 2026)
The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP) marks a fundamental transformation of Indonesia’s criminal law system toward a nationally codified framework grounded in corrective, rehabilitative, and restorative justice. The transitional period prior to its full implementation presents challenges for legal higher education institutions, which have traditionally been oriented toward the Wetboek van Strafrecht (WvS). This study analyzes the challenges of integrating the 2023 KUHP into the curriculum and explores adaptation strategies among academic communities. A normative juridical method with conceptual and comparative approaches is employed to examine differences between the old and new Criminal Codes, as well as curriculum policies. The findings reveal three main issues: dualism in teaching materials, the need to reorient lecturers’ understanding of new legal principles, and the limited availability of supporting literature. The integration of the 2023 KUHP requires an integrative curriculum reform and a transformation of legal mindset; therefore, higher education institutions must align their curricula and strengthen academic discourse to prepare graduates who are adaptive to legal developments.